Sex differences in readmission rate after cardiac surgery - Luca Koechlin; Jules Miazza; Brigitta Gahl; Brigitta Gahl; David Santer; David Santer; Luise Vöhringer; Denis Berdajs; Denis Berdajs; Friedrich S. Eckstein; Friedrich S. Eckstein; Oliver Reuthebuch; et al. (Frontiers in Cardiovascular Medicine, 2023)
IntroductionThe impact of sex on hospital readmission rate after cardiac surgery is unclear. Therefore, we aimed to analyse sex-specific differences and underlying factors in 30-day readmission rate after cardiac surgery.MethodsWe conducted a single center study including all patients after major cardiac surgery (excluding aortic dissection and left ventricular assist device implantation) from January 2012 to September 2020. Reasons for readmission were adjudicated according to all available medical records. We calculated incidence rate ratios (IRR) with 95% confidence intervals (CI) for female sex with re-admission crude and adjusted for plausible confounding factors using negative binomial regression.Results4,868 patients were included in the analysis. The median [Interquartile range] age was 68 [60 to 74] years and 24% (n = 1,149) of the patients were female. Female patients were significantly older (median [IQR] age 70 (63 to 76) vs. 67 (59 to 74), p < 0.001) and had lower body mass index and fewer cardiovascular risk factors compared to men. Isolated valve surgery was more frequent in female while coronary artery bypass grafting was more often in men. 30-day readmission was comparable between both sexes (7.0% [n = 81] in female vs. 8.7% [n = 322] in men; p = 0.078). Cardiac related readmissions and infections were the most common reasons for readmission in both groups. The overall incidence rate ratios of female sex with readmission (0.80, 95% CI 0.63 to 1.03, p = 0.078) remained robust after adjustment for EuroSCORE 2 (0.78, CI 0.61 to 1.0, p = 0.051).ConclusionReadmission rate and reasons for 30-day readmission after major cardiac surgery were similar between men and women.